Dynamics o f Thunderstorms Part II – Origin of downdrafts in a thunderstorm and the circulation in a full-fledged thunderstorm cell - Mull, S.; RAO, Y.P. (MAUSAM, 1950)
The present explanation for downdraft in Airmass Thunderstorm does not account why all Cumulonimbus clouds do not culminate in a full-fledged thunderstorm. An alternative explanation is offered based on the development of instability within the cloud as a result of the sudden congellation of the supercooled layer.